Pelatihan KKM (Kepala Kamar Mesin) Bagi Nelayan di Kecamatan Kragan Kabupaten Rembang Jawa Tengah - Eko Wismo Winarto; Harjono Harjono; Lava Himawan (Jurnal Pengabdian dan Pengembangan Masyarakat, 2018)
The diesel engine lifespan increasing in marine operation will decrease their perfomance.  Some problems will occur, there are hard starting, bad exhaust gas colour and bad power output, suddenly engine stop and hard to start back. There fore any diesel engine training is needed to guard engine perfome. The KKM (Ketua Kamar Mesin= engine room head) training for maintaining their ability to serve diesel engine properly is necesary.   Their ability have came from their friend or autodidact. The 25 fishingman ships were burning at Blora quay last several mounths prove of the lack of their ability. Thre are some rutine maintenances sould be done; every 8 hours Radiator water, diesel fuel and lubricantion oil are controlled, every week (150 hours) air screen cleaning, every two weeks (250 hours) oil lubricant replacement. Every month (500 hours) readjust fuel valve, every 1000 hours oil lubricant replacement and garvernor funtion checking, every 1500 hours inlet manifold cleaning and exhaust sistem, every 3000 fuel tank cleaning and to overhaul also replacement worn out spare parts, every 6000 hours cylinder head take apart and carbonation, and every 12000 hours general over haul and replacement worn out spare part.